Establishing Standards on Colors from Natural Sources. Issue 11 (14th October 2017) - Simon, James E.; Decker, Eric A.; Ferruzzi, Mario G.; Giusti, M. Monica; Mejia, Carla D.; Goldschmidt, Mark; Talcott, Stephen T.
Abstract: Color additives are applied to many food, drug, and cosmetic products. With up to 85% of consumer buying decisions potentially influenced by color, appropriate application of color additives and their safety is critical. Color additives are defined by the U.S. Federal Food, Drug, and Cosmetic Act (FD&C Act) as any dye, pigment, or substance that can impart color to a food, drug, or cosmetic or to the human body. Under current U.S. Food and Drug Administration (FDA) regulations, colors fall into 2 categories as those subject to an FDA certification process and those that are exempt from certification often referred to as "natural" colors by consumers because they are sourced from plants, minerals, and animals. Certified colors have been used for decades in food and beverage products, but consumer interest in natural colors is leading market applications. However, the popularity of natural colors has also opened a door for both unintentional and intentional economic adulteration. Whereas FDA certifications for synthetic dyes and lakes involve strict quality control, natural colors are not evaluated by the FDA and often lack clear definitions and industry accepted quality and safety specifications. A significant risk of adulteration of natural colors exists, ranging from simple misbranding or misuse of the term "natural" on a product label to potentially serious cases of physical, chemical, and/or microbial contamination from raw material sources, improper processing methods, or intentional postproduction adulteration. Consistent industry‐wide safety standards are needed to address the manufacturing, processing, application, and international trade of colors from natural sources to ensure quality and safety throughout the supply chain.